(untitled) (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. Students’ lifestyle and daily routines change at the moment of entering higher education institutions, their load for mental activity increases, whereas physical activity decreases. It becomes complicated to maintain proper health, necessary levels of physical development, fitness and functional potential (Daledo et al., 2008). The analysis of previously conducted research on physical activity of students at Lithuanian universities showed that motivation to individually engage in sports and be physically active has dropped. Abound 40.0% of university students have no stimulus for physical self-improvement and almost do not spend time for exercising (Poteliūnienė et al., 2005). The attitudes of the majority of students towards physical activity are negative – about 92.0% of females and 91.0% of males claim that they do not approve of compulsory physical activities and slightly more than half of females (51.0%) and a lower percentage of males (44.0%) expressed doubt in relation to their intent of being physically active throughout an entire period of studying (Dadelo et al., 2008). There is still a gap in research analysing such situation among students of Klaipėda University. There were also no studies found which would analyse the attitudes towards physical activity expressed by students of Klaipėda University. Hypothesis: Klaipėda university female students engage in sports less frequently compared to male students. Research aim was to reveal the attitudes towards physical activity of students disengaged in sport at Klaipėda University. Research methods. Quantitative research was conducted using the method of questionnaire survey in October of 2011. A probability random sample was comprised of 203 (104 males and 99 females) first year full-time students, disengaged in sports, aged 19–21 years. Research results show that 70.9% of females and 49.0% of males lack knowledge about physical activity. One third of academic youth do not dedicate a decent share of time for their physical self-improvement, and less than one fifth of students are completely disengaged in sports activities; 30.7% of males and 30.7% of females name a lack of informal physical education clubs which would be free of charge as the main reason for their disengagement in sport-related activities. Supposedly this is the reason why more than two thirds of men and women are absolutely willing to refuse compulsory exercising. Discussion and conclusions. The results of the conducted research allow concluding that the attitudes towards physical activity expressed by the majority of Klaipėda University students are poor. It has been revealed that the academic community neglects proper development of students’ attitudes towards physical activity by deciding to deprive students of sufficient information. Therefore, the results highlighted a lack of such knowledge among students. Drawing on the conducted research results we suggest that application of methodological research materials will create better conditions to develop physical activity and especially physical self-improvement of Klaipėda university students providing more subject-related and methodological knowledge. Keywords: physical activity, attitude, physical self-improvement.